Preoperative Predictors of Response to Hypoglossal Nerve Stimulation for Obstructive Sleep Apnea. (21st January 2020) - Xiao, Roy; Trask, Douglas K.; Kominsky, Alan H.
Abstract : Objective: Hypoglossal nerve stimulation (HGNS) is an effective treatment for patients with obstructive sleep apnea (OSA) who fail continuous positive airway pressure (CPAP). We assessed the relationship between patient characteristics and response to HGNS. Study Design: Retrospective cohort study. Setting: Single tertiary care institution. Subjects and Methods: This study included CPAP‐intolerant patients with moderate to severe OSA after HGNS system implantation from November 2015 to December 2017. Patient measures, drug‐induced sleep endoscopy (DISE) findings, and apnea‐hypopnea indices (AHIs) were recorded. Results: Forty‐eight patients underwent implantation with the following median measures: age, 66 years; body mass index, 28.6; and neck circumference, 41.0 cm. Patients were classified by Friedman tongue position (II, 27%; III, 56%; IV, 17%) and Mallampati grade (I, 25%; II, 50%; III, 23%; IV, 2%). By DISE, 71% had anterior‐posterior palatal collapse. Additionally, 38% had lateral oropharynx collapse; 50%, tongue base collapse; and 27%, epiglottis collapse. Following implantation, median AHI improved from 38.5 to 2.7 ( P <. 001), and 92% of patients had no worse than mild OSA (8% moderate). Patients with Friedman tongue position grade II/III experienced greater change in AHI as compared with grade IV (94.2% vs 73.8%, P <. 001). Patients with Mallampati score I/II experienced greater improvement versus score III/IV (94.7% vs 66.5%, P <. 001). No DISE findings, including any obstruction or collapse, were associated with change in AHI. Conclusion: This study further confirms HGNS as an effective treatment of CPAP‐intolerant OSA. Office measures such as Friedman tongue position IV and Mallampati III/IV were associated with mildly decreased response. DISE findings were not associated with patient response.